The JESTKOD database: an affective multimodal database of dyadic interactions. - Bozkurt, Elif; Khaki, Hossein; Keçeci, Sinan; Türker, B.; Yemez, Yücel; Erzin, Engin (Language Resources & Evaluation, 2017)
In human-to-human communication, gesture and speech co-exist in time with a tight synchrony, and gestures are often utilized to complement or to emphasize speech. In human-computer interaction systems, natural, affective and believable use of gestures would be a valuable key component in adopting and emphasizing human-centered aspects. However, natural and affective multimodal data, for studying computational models of gesture and speech, is limited. In this study, we introduce the JESTKOD database, which consists of speech and full-body motion capture data recordings in dyadic interaction setting under agreement and disagreement scenarios. Participants of the dyadic interactions are native Turkish speakers and recordings of each participant are rated in dimensional affect space. We present our multimodal data collection and annotation process, as well as our preliminary experimental studies on agreement/disagreement classification of dyadic interactions using body gesture and speech data. The JESTKOD database provides a valuable asset to investigate gesture and speech towards designing more natural and affective human-computer interaction systems.